MILITARY FACTOR AND NON-MILITARY ASPECTS IN MODERN INTERNATIONAL AND REGIONAL RELATIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article briefly examines and analyzes military factors and non-military aspects in modern world politics, as military and armed conflicts are increasing in the world every year, as well as the opinion of military experts in this field. The difference between previous military conflicts and conflicts of the 21st century and the approximate number of military conflicts in the world as of 2024. The article also analyzes the evolution of military technologies in the field of digitalization, intelligence activities, high-precision munitions and other aspects of military technology. In addition, the article examines non-military aspects such as political and diplomatic; economic; information and psychological, legal and humanitarian measures with brief definitions. Participation of UN departmental departments such as the World Food Program, the Office of the High Commissioner for Refugees and peacekeeping units of member states and other issues related to military and non-military aspects.
Keywords: military and non-military aspects, WFP, OHCHR, modern military technologies, military conflicts, information warfare.